“Sedentarisation” of transhumant pastoralists results in privatization of resources and soil fertility decline in West Africa's cotton belt - G. I. Anita Dossouhoui; G. I. Anita Dossouhoui; Pierrot Lionel Yemadje; Pierrot Lionel Yemadje; Rodrigue V. Cao Diogo; Oumarou Balarabe; Oumarou Balarabe; Pablo Tittonell; Pablo Tittonell (Frontiers in Sustainable Food Systems, 2023)
Transhumant pastoralism is an ancient natural resource management system traditionally connecting ecosystems across north-south precipitation gradients in West Africa. As rural population grew, several governments in the region have promoted their settlement, i.e., the “sedentarisation” of nomadic pastoral peoples to avoid conflict over land use and access to resources with local sedentary populations. Former transhumant pastoralists settled down and started growing crops using the manure of their livestock. This led to the dwindling of traditional agreements and exchanges (manure against crop residues) between pastoralists and agriculturalists, that resulted in less nutrients flowing between livestock, food crops and the main cash crop in the region: cotton. As a consequence, soil fertility declined, grazing areas are overexploited, and crop production is increasingly dependent on mineral fertilizers, which are produced outside the region, exposing the livelihood of local farmers to the volatility of international (oil) markets. How do local farmers perceive the effect of this virtual “privatization” of natural resources? Is the production of cotton, a main agricultural export of west African countries, a viable option in this new situation? What does this imply for the research and policy agendas to support agricultural development? We explored these questions through engaging in discussion with farmers, herders and extension agents in three cotton growing zones of Benin.